Empowering children : play-based curriculum for lifelong learning - Shipley, Dale. ([Place of publication not identified] Nelson Education, 2013)
The fifth edition continuous to assume that student learn more efficiently when clear links are made between theory and practice. This textbook does not embrace a particular model for practice.
I: Setting the scene: perspectives and contexts related play -- II: Planning play and learning environments -- III: Curriculum for young children -- IV: Facilitating symbolic play -- V: Play and learning-to-learn -- VI: Creative play -- VII: Active learning in the natural world -- VIII: Empowering children through play.
Includes bibliographical references and index.
Keywords: EARLY CHILDHOOD EDUCATION; CURRICULUM PLANNING; PLAY